2021
DOI: 10.7150/thno.60582
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-targeted intraoperative fluorescence imaging detects high-grade glioma with panitumumab-IRDye800 in a phase 1 clinical trial

Abstract: Rationale : First-line therapy for high-grade gliomas (HGGs) includes maximal safe surgical resection. The extent of resection predicts overall survival, but current neuroimaging approaches lack tumor specificity. The epidermal growth factor receptor (EGFR) is a highly expressed HGG biomarker. We evaluated the safety and feasibility of an anti-EGFR antibody, panitumuab-IRDye800, at subtherapeutic doses as an imaging agent for HGG. Methods : Eleven patients with contrast-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
(66 reference statements)
1
25
0
Order By: Relevance
“…Despite their prevalence in optical imaging probes, BODIPY dyes exhibit excitation and emission bands lying in the < 600 nm range, which is suboptimal for intraoperative imaging; therefore, future scaffold designs may consider integrating dyes that excite/emit in the near infrared (NIR) I (650–900 nm) or NIR II (1000–1500 nm) windows (Ariztia et al 2022 ; He et al 2018 ). For example, fluorophores such as IRDye800 (Rosenthal et al 2015 ; Zhou et al 2021 ) or cyanine dyes (e.g., Cy5.5 (Tsai et al 2018 ; Kang et al 2016 )) have been used (pre-)clinically, and will be considered when designing our next generation of multi-modal scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their prevalence in optical imaging probes, BODIPY dyes exhibit excitation and emission bands lying in the < 600 nm range, which is suboptimal for intraoperative imaging; therefore, future scaffold designs may consider integrating dyes that excite/emit in the near infrared (NIR) I (650–900 nm) or NIR II (1000–1500 nm) windows (Ariztia et al 2022 ; He et al 2018 ). For example, fluorophores such as IRDye800 (Rosenthal et al 2015 ; Zhou et al 2021 ) or cyanine dyes (e.g., Cy5.5 (Tsai et al 2018 ; Kang et al 2016 )) have been used (pre-)clinically, and will be considered when designing our next generation of multi-modal scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-targeted fluorescent imaging has been tested in clinical trials for several types of cancer, including head and neck cancer [ 25 ], pancreatic cancer [ 26 ], glioblastoma and glioma [ 13 , 27 ], oral cancer [ 28 ], and lung cancer [ 13 ]. Fluorescence-guided surgical imaging using panitumumab, an EGFR antibody, conjugated to IRDye800 was used to detect gliomas in real time [ 29 ], demonstrating good tumor-to-background contrast ratio. The same antibody was used in a murine model of colorectal cancer for fluorescence-guided surgery with a strong fluorescent contrast [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marston et al studied panitumumab-IRDye800 in mice with subcutaneous CRC and found that the molecule resulted in a significantly higher TBR in all three models compared to a nonspecific IgG-IRDye800 [ 102 ]. This conjugate has been well evaluated in preclinical and clinical studies of head and neck cancer [ 103 , 104 , 105 , 106 ], pancreatic cancer [ 107 , 108 , 109 ], and brain cancer [ 110 , 111 ]. A study using cetuximab-IRDye800 for locally advanced rectal cancer (TRACT-II) is ongoing in the Netherlands (NCT04638036).…”
Section: Egfrmentioning
confidence: 99%